JASLARDÍ MILLIY IDEYA RUWXÍNDA TÁRBIYALAWDA XALÍQ AWÍZEKI DÓRETIWSHILIGINIŃ ORNÍ HÁM ÁHIMIYETI - Ametov, A.Q.; Nzamatdinov, N. (SCIENCE and SOCIETY, 2022)
This article reveals the importance of examples of folk art in educating the young generation in the spirit of the national ideal. Also, examples of folk art are explained theoretically. In particular, the impact of folklore is analyzed, epics, proverbs, and riddles on the spiritual education of young people.